Implementation Of Prophetic Leadership Values In Human Resource Management In The Digital Era - Syuhada, Wira; 'Ainulyaqin, Muhammad Hamdan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Digital transformation has introduced new challenges in human resource management, necessitating an adaptive leadership style that also upholds core values. This study investigates and analyzes how prophetic leadership values can be applied in contemporary human resource management by interpreting leadership verses from the Qur'an*. Employing a qualitative methodology that combines thematic interpretation and content analysis, the research focuses on 47 Quranic verses that pertain to leadership, correlating them with modern HRM principles. The findings highlight five key prophetic leadership values that are pertinent to HRM in today's digital landscape: (1) al-'adalah (justice) in reward and performance management, (2) al-amanah (trust) in talent management, (3) at-tawazun (balance) in work-life integration, (4) al-hikmah (wisdom) in decision-making processes, and (5) al-mas'uliyyah (accountability) in governance systems. The proposed implementation model offers a new framework for embedding prophetic values into digital HRM practices, structured around three levels of transformation: mindset, systems, and technology. This research enhances the Sharia management knowledge base and provides practical solutions for organizations to align digital transformation with Islamic leadership principles.